Elevated high sensitive C-reactive protein in fibromyalgia - Beiner, Eva; Brenner Miguel, Sergio Filipe; Friederich, Hans-Christoph; Tesarz, Jonas (Frontiers in psychiatry, 2023)
IntroductionFibromyalgia syndrome (FMS) is a complex chronic pain condition characterized by widespread pain and tenderness, fatigue, and sleep disturbances. Currently, factors contributing to FMS are considered to be multifactorial, and the involvement of inflammatory processes is a question of debate.ObjectiveThe aims of this study were (1) to assess whether serum concentrations of high-sensitivity C-reactive protein (hsCRP) differ between individuals diagnosed with FMS and pain-free controls, (2) to determine whether these differences are associated with clinical symptoms, and (3) to explore whether the observed differences can be explained by specific covariates such as age, weight, and smoking status.MethodsAn ANOVA was applied to identify differences of hsCRP levels between FMS and pain-free controls and an analysis of covariance (ANCOVA) was performed to investigate the dependencies of hsCRP with respect to covariates. To assess the reliability of our findings, we also utilized a Bayesian robust estimation model to determine the level of confidence associated with our results.ResultsThe results showed that individuals with FMS had higher hsCRP levels compared to healthy controls [F(1,106) = 8.802, p < 0.001] and that higher hsCRP levels were significant correlated with a higher symptom burden (r = 0. 287, p = 0.008) and more tender points (r = 0.307, p = 0.005). Further, hsCRP levels were significantly associated with weight (η2 = 0.154, p < 0.001), but independent of age (η2 = 0.005, p = 0.42), smoking status (η2 = 0.002, p = 0.623), or gender (η2 = 0.0045, p = 0.437), which resulted in an insignificant group effect between FMS and controls (η2 = 0.029, p = 0.052), even after controlling for covariates.ConclusionIn conclusion, this study provides evidence that sub-inflammatory processes correlate with clinical symptoms, which can be partly attributed to differences in weight, but cannot be fully explained by them. Further research is needed to elucidate the mechanisms underlying the association between hsCRP and FMS and to explore the potential therapeutic implications of targeting hsCRP in the management of FMS.